Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1021/ef800537a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Pyrolysis Behavior of Novel Anthracene Oil Derivatives

Abstract: The characterization and pyrolysis behavior of a set of pitches prepared from anthracene oil have been described. The pitches were obtained from four successive cycles of a sequential process that begins with blowing air through the heated anthracene oil, to bring about recombination reactions. Reaction products are distilled to give a pitch residue and a lighter fraction. Thermal treatment/distillation cycles of this reaction product yield a pitch and a distillate fraction (unreacted anthracene oil) during ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 22 publications
5
27
0
Order By: Relevance
“…Two cokes of different optical texture (mosaics and flow domains) obtained from two synthetic pitches prepared from the same coal fraction at different conditions [12] were ground in an agate ball mill at 400 rpm for 1 h, and then sieved through a 0.75 μm mesh. The resultant powders from each coke were graphitized at 2800 °C in a graphite furnace for 45 min under argon flow to provide two graphites, G1 and G2.…”
Section: Preparation Of Graphitesmentioning
confidence: 99%
“…Two cokes of different optical texture (mosaics and flow domains) obtained from two synthetic pitches prepared from the same coal fraction at different conditions [12] were ground in an agate ball mill at 400 rpm for 1 h, and then sieved through a 0.75 μm mesh. The resultant powders from each coke were graphitized at 2800 °C in a graphite furnace for 45 min under argon flow to provide two graphites, G1 and G2.…”
Section: Preparation Of Graphitesmentioning
confidence: 99%
“…Further evidence of the importance of the benzylic position and oxygen in condensation reactions comes from research on the production of synthetic pitches from coal tar derived anthracene oil. 31,40,41 In that work anthracene oil was air blown at 280-300 C in the presence of an iron chloride catalyst. It was found that the incorporation of oxygen groups into aromatic side chains of the anthracene oil molecules was important for improving the yield of higher mass compounds (500 to >3000 amu) compared to nitrogen blown conditions.…”
Section: Gas Compositions After Reactionmentioning
confidence: 99%
“…In samples with large polydispersity like these pitches, signal from higher molecular weight materials is overshadowed by that of the more abundant lighter species. Fractionation allows then a more accurate determination of the range of molecular weights present in the sample [6].…”
Section: Molecular Weight Determination Of Anthracene Oil-derived Pitmentioning
confidence: 99%
“…However, the use of traditional fibres, e.g., PAN-based carbon fibres, for these applications is not possible due to both their low volume of production and prohibitive cost. The use of synthetic pitches from a low cost carbon-rich source such as anthracene oil has been proposed as an alternative for the production of this kind of fibres [6].…”
Section: Introductionmentioning
confidence: 99%